Estudo visando a síntese de intermediários enóis éteres via reações de α-sulfenilação - (:unkn) unknown (Universidade Estadual de Goiás, 2013)
The reactive intermediates, enols ethers, are used in several synthetic routes, they can be obtained of the nature or synthesized in the laboratory. These compounds present potentialities for numerous pharmacological applications such as antibacterial, antifungal, cytotoxic, phytotoxic, among others. The focus of this work was to develop an alternative synthetic route to enol ether 32 by way of reaction of α- sulfenylation. The organosulfur compounds are fairly applied in syntheses of biologically active substances, of this form, the reactions of α-sulfenylation arose an alternative in the preparation of new reactive intermediates. In the ambit of this work, realized the synthesis of the compound 2,6-dioxo-9-oxabicyclo [3.3.1]-nonane (28) starting from the 9-oxabicyclo [3.3.1]-nonane-2,6-diol (27) through an oxidation with IBX. The diketone 28 was subjected to reactions of α-halogenation and α- sulfenylation in the attempt to produce the 3,7-bis-phenylthio-9-oxa-bicyclo [3.3.1] nonane-2,6-dione (57). With relationship the diketone 28, there was only the sulfenylation on one side. The structures of the compounds, diol 27 and diketone 28 obtained were analyzed and confirmed by infrared spectra (IR) and nuclear magnetic resonance of hydrogen (1H NMR). The bioassay carried with the diketone 28, in vitro, for evaluation of the biological potential front E. coli, S. aureus and C. albicans, which was verified that the sample didn't demonstrate antibacterial and antifungal activity.
Keywords: Enol éter; Macrolídeos; α-sulfenilação; Bioensaios; Enol ether; Macrolides; α-sulfenylation; Bioassays; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::QUIMICA ORGANICA